Analisis Etika Biomedis Terhadap Pasien Transgender dalam Mengakses Layanan Kesehatan di Yogyakarta - Rona Utami; Rizky Anandasigit Nugraha; Moch Najib Yuliantoro; Hastanti Widy Nugroho (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2020)
This research focuses on transgender patients discrimination in Yogyakarta in accessing healthcare services. There are two questions on this research: what is the obstacle faced by the transgender-patients in accessing healthcare services? How is the analysis of biomedical ethics seeing this issue? Theresults on this research are despite the facttheywere notbeing discriminated inthehospital, they did not getthe health insurance by the governmentbecause of the administrative issuewhichcan not accommodatetheir genderchoice. Therefore, this researchseeks to understand the barriers of transgender patients in accessing healthcareservices through the perspective of biomedical ethics ofTom L. Beauchamp and James Childress. The researcher concludes that thegeneral ruleon social benefitsappliedin society isstill limitedonlyto the specificgenders. Itis not in accordance with the two principles in biomedical ethics:the principle of justice states that the transgender who is physically harmedhasright to getsocial benefitsto remedy the effect of thedisadvantagesdue to theirnatural property and to have more equal chance of life;and the principle of autonomy states that an autonomous decision of the transgender people to choose their gender is related to the individual rightsalthough they have different view with others andas long as their action do not leave the disadvantage toothers,it must be respected as a moral obligation.